Date rape a violation of trust - Jackson, Lisa.; Alboum, Scott; Cambridge Educational (Firm).; Rider University. Television Studio; Films for the Humanities & Sciences (Princeton, N.J. : Films Media Group, 2008)
Examines the myths and facts of date or acquaintance rape.
What is rape -- Rules of the game -- The trauma of rape -- Date rape drugs -- Protecting yourself -- If you or someone you love .
Executive producer, Lisa Jackson ; director Scott Alboum.
Keywords: Rape -- Prevention; Acquaintance rape; Films for the hearing impaired